Potential of wild edible fruits for nutrition in indigenous communities of Northwest Himalaya, India - Singh, Joginder; Rajasekaran, A.; Negi, A. K.; Pala, Nazir A.; Panwar, Vijender P.; Bussmann, Rainer W.; Malik, Zubair A. (Ethnobotany Research and Applications, 2023)
Background: In the rural areas of Himachal Pradesh, poor and tribal people depend on a variety of wild plants, animals, and fungi for their own consumption and for income generation. Despite their role in bridging periods of food shortages and providing dietary variety, most of wild edible plants are not accessed for nutritional potential. This is particularly true for the district of Kinnaur (a predominantly tribal area) of Himachal Pradesh. Hence, the present study was carried out to study the nutrient content of ten wild edible fruit species growing in the district of Kinnaur. The species included Berberis aristata, Elaeagnus umbellata, Hippophae salicifolia, Malus baccata, Prunus cornuta, Prunus persica, Pyrus pashia, Ramaria botrytis, Rosa webbiana and Viburnum cotinifolium. Methods: The samples collected from the identified plants were cleaned, dried, powdered and stored in airtight containers for laboratory analysis. Fresh fruit pulp was used for measurement of pH, titratable acidity, total soluble solids (TSS) and ascorbic acid. Fresh weight of fruit pulp was recorded by using a digital balance and the samples were later oven dried (60°C) for moisture content determination (AOAC, 2006). All the dried samples were pulverized in pestle and mortar into fine powder separately and stored in airtight containers, free from contamination till other parameters were determined. All the parameters were evaluated in triplicates, results were analyzed by using descriptive statistics and reported as mean ± standard error. Results: The moisture content of the fruits varied from 58.76% to 89.75% while pH values ranged from 2.91 to 3.86. The crude protein of species varied between 0.38% - 4.58%. Prunus cornuta contained high amount of total soluble solids, TSS (18.53o Brix). The acidity in the fruits ranged between 0.47-2.73%. The total carbohydrate content varied between 19.52% and 78.40%. The highest sugars (7.60%) were observed in the fruits of Viburnum cotinifolium. Total phenols ranged in between 0.26-1.47%. The maximum ascorbic acid content and antioxidant activity was recorded in fruits of Hippophae salicifolia. These wild edible plants had also significant amounts of minerals. Conclusion: The study shows that these wild edible plant species are good sources of nutrition for rural population. Keeping in view the nutritional values and commercial potential, these important species need to be conserved in their natural habitats and should be included in traditional agricultural systems. Domestication of these species will not only improve the economic condition of the local people but also aid in the conservation of biodiversity. Key words: Wild edible plants, nutritive values, domestication, conservation.